Analizing The English Teacher Talk In Efl Classroom Interaction - Siregar, Khoniatun Nisa; Lismay, Lely (PT. Marosk Zada Cemerlang, 2023)
The study used qualitative research design. The purpose of this study was to identify and explore information about teachers' conversation in classroom interaction at SMAN 1 Banuhampu. The key informant of this research is the 11th grade English teacher at SMAN 1 Banuhampu. Furthermore, the supporting informants are the 11th grade students of SMAN 1 Banuhampu. To collect data, observation and interview were used. Based on the findings, the research questions are answered. First, what are the formal features of teachers' speech? The formal features of teachers' speech in class 11 of SMAN 1 Banuhampu are that teachers have slow speaking speed, long pauses, frequent pauses, exaggerated pronunciation, simplified pronunciation, basic vocabulary, slow level of subordination, declarative statements that are often repeated, and often independent. Furthermore, the functional features of teacher speaking in class 11 of SMAN 1 Banuhampu are that the teacher speaks the most in class I, the teacher uses teacher speech in asking questions, and the teacher also uses teacher speech in giving feedback.